United Kingdom : 2006 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for United Kingdom. (IMF Staff Country Reports; Country Report, 2007)
This 2006 Article IV Consultation highlights that macroeconomic performance in the United Kingdom remains impressive. After softer growth in 2005, the acceleration in GDP in 2006 was broadly based. Business investment was boosted by high net rates of return; private consumption by robust employment growth, steady wage growth, and rising household wealth; and exports by the recovery in the euro area. Most indicators suggest little economic slack as of end-2006. The financial sector continues to thrive, and linkages with financial systems in other countries continue to grow.